Study on the behavioral decision of multiple subjects of agricultural green production under the double carbon target in China - Xiaoli Zhang; Xiaoli Zhang; Xiuli Duan; Xinhe Zhou; Zhengfei Pang; Hongcheng Duan; Yun Teng; Hui Xu (Frontiers in Public Health, 2025)
Excessive carbon emissions constitute a major driver of contemporary global warming. Achieving carbon neutrality in agriculture, particularly via carbon peaking, represents a critical strategy for emission reduction, wherein green agricultural production serves as a pivotal component. This study constructs a unified model encompassing the government, agricultural enterprises, and farms engaged in green agricultural production, utilizing a dynamic evolutionary game approach to examine the decision-making behaviors of these stakeholders. The findings indicate that green agricultural production entails the responsibilities of managers, users, and producers. The government fulfills a guiding and supervisory role, while agricultural enterprises actively produce low-carbon agricultural materials, and farms rigorously implement these materials. To facilitate this, the government should implement a reward and punishment mechanism, including increased carbon tax rebates for enterprises producing low-carbon materials and subsidies for farms utilizing them. Conversely, penalties should be levied on entities that fail to comply with low-carbon practices. The government must meticulously calibrate subsidies and fines within a reasonable range, appropriately reduce taxes, and effectively manage regulatory costs to mitigate financial strain. Under government incentives and penalties, agricultural enterprises should proactively respond by offering price concessions to farms utilizing low-carbon materials, balancing costs and benefits, and fostering a socially responsible corporate image. Farms should establish close collaboration with the government and enterprises to ensure the procurement, utilization, and production of low-carbon agricultural materials. This study provides valuable insights for advancing agricultural carbon neutrality through the perspective of green agricultural production.